Perceived Leader-Member Exchange and Patient Safety Culture among Nurses in Tertiary Hospitals, Kunming, the People’s Republic of China - Zhang, Ling; ทั้งเจริญกุล เพชรสุนีย์; จิตต์ภักดี บุญพิชชา (Nursing Journal CMU, 2019)
Patient safety culture is critical for hospitals to prevent adverse events occurring. However, gaps still remain regarding the relationship between leader-member exchange and patient safety culture in China. The purposes of this study were to describe leader-member exchange and patient safety culture in China, and to examine the relationship between leader-member exchange and each dimension of patient safety culture in tertiary hospitals in Kunming, the People’s Republic of China. The research sample consisted of 315 nurses, representing 105 wards. The research instruments included: 1) Demographic Data Form, 2) the Multi-Dimensional Leader-Member Exchange Scale (LMX-MDM) developed by Liden and Maslyn (1998), and 3) Hospital Survey on Patient Safety Culture (HSOPSC) developed by Sorra and Nieva (2004). The Cronbach’s alpha coefficients for LMX-MDM and HSOPSC were .98 and .91 respectively. Data were analyzed using descriptive statistics and Spearman’s Rank-Order Correlation Coefficient. The findings of this study were as follows: Approximately 77% of the wards had a high level of leader-member exchange, while the rest had a moderate level of leader-member exchange. Approximately 22% of the wards had a strength area in overall patient safety culture. About 65% had a moderate area in overall patient safety culture, while 13% of the wards need improve in overall patient safety culture. There was a positive relationship between leader-member exchange and the subscales of patient safety culture, except in the case of the subscale of hospital handoffs and transition. The results of this study could provide valuable information for hospital administration and nurse managers to be aware of the importance of patient safety culture and to set up interventions to enhance leader-member exchange in order to promote patient safety culture.